The caries pattern of tooth surface of children at SDN Mangaran 2 in Kebun Renteng, Jember Regency: Pola karies berdasarkan lokasi permukaan gigi anak SDN Mangaran di wilayah Kebun Renteng Kabupaten Jember - Qatrin Yulia Safitri; Roedy Budirahardjo; Niken Probosari; Sulistiyani (Makassar Dental Journal, 2022)
Objective: To determine the caries pattern of tooth surface of children at SDN Mangaran 2 in Kebun Renteng Jember. Methods: Descriptive observational with a cross sectional approach. The sample were students of class I-III totaling 38 students with a total sampling technique. The data were discussed descriptively and presented in tabular form. Results: Caries in primary teeth was more common on the mesial surface and the least on the facial or buccal surface; whereas caries in permanent teeth was more common on the occlusal surface. Conclusion: The mesial surface is the most caries-prone surface in primary teeth, while in permanent teeth it is the occlusal surface